Epidemiology of Child Maltreatment during the COVID-19 Pandemic in Saudi Arabia - Shuliweeh Alenezi; Mahdi A. Alnamnakani; Mohamad-Hani Temsah; Rozan Murshid; Fahad Alfahad; Haitham Alqurashi; Hana Alonazy; Mohamad Alothman; Majid Aleissa (MDPI AG, 2022)
Child maltreatment, especially during health crises, is a major public health issue transcending cultural, social, and racial contexts. We assessed the sociodemographic and related risk factors associated with the types and rates of child maltreatment. We also assessed the economic, social, and environmental characteristics of child maltreatment victims and their perpetrators, as they were reported to the Saudi National Family Safety Program (NFSP), with consideration of the COVID-19 pandemic's impact. A secondary data analysis of a retrospective review was conducted to compare types and rates before and during the COVID-19 outbreak, utilizing descriptive and multivariate analyses on anonymized data from the NFSP. According to a predetermined list of relevant risk factors for child maltreatment outlined by the NFSP, these anonymized data were obtained and analyzed with no exclusion criteria (n = 1304). The findings showed that a child's age correlated significantly and positively with their odds of being physically maltreated; as a child's age increased by one year, on average, their corresponding predicted odds of being physically maltreatment tended to rise by a factor equal to 7.6% (p < 0.001). Neglected children, compared to those who had not been previously neglected, were predicted to be almost twice (2.23 times more) as likely to be victims of physical maltreatment on average (p < 0.001). Children were notably more likely to experience sexual abuse during the COVID-19 pandemic than those exposed to abuse during the period before (1.69 times). The COVID-19 pandemic was associated with significantly lower odds of physical child maltreatment (47.7% less). This study found no statistically significant effect of the COVID-19 pandemic on children's odds of being emotionally maltreated (p = 0.169). These findings support the existence of specific risk factors for child maltreatment for both child victims and perpetrators. They also attest to the significant differences between different types of maltreatment. A systematic, proactive system is needed to screen and document child maltreatment with a higher degree of integration with community reporting systems.